The Role of Stigma and Denormalization in Suicide-Prevention Laws in East Asia: A Sociocultural, Historical, and Ethical Perspective. Issue 5 (September 2017) - Chen, Justin A.; Courtwright, Andrew; Wu, Kevin Chien-Chang
Abstract : Abstract: In many Western countries, the criminalization and stigmatization of suicide has given way to a biomedical approach aimed at destigmatizing suicide and treating underlying mental illness. By contrast, in many East Asian countries, suicide has never historically been criminalized or stigmatized. High rates of suicide in Japan, South Korea, and Taiwan have recently led policy makers in those countries to pursue innovative suicide-prevention strategies. The intentional denormalization of harmful behaviors has been discussed in the public health and ethics literatures, particularly with regard to smoking cessation, and could represent a novel mechanism for preventing suicides in East Asia. Using examples from the sociocultural, historical, and legal discourses surrounding suicide in Western and East Asian contexts, we suggest that denormalization can be a justified, culturally relevant suicide-prevention strategy, but that care must be taken to avoid shaming or stigmatizing suicidal individuals. Specifically, we propose the term weak denormalization to refer to an ethically permissible strategy at the mildest end of a spectrum of denormalizing approaches—milder than the reintegrative shaming described in the criminal justice literature, and diametrically opposed to outright stigmatization, which is generally considered ethically impermissible. Given the severe stigma of mental illness in East Asia, adopting the dominant Western view of suicide as solely a psychiatric concern would not be justified. Weak denormalization strategies in East Asia should be culturally tailored and rigorously tested on a small scale. They should include social supports, praise for the bravery of those of who seek help, and strategies to reduce shame regarding perceived social failure.